1998
DOI: 10.1074/jbc.273.38.24592
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Endocytosis of G-protein-coupled Receptors by a Biochemically and Functionally Distinct Subpopulation of Clathrin-coated Pits

Abstract: ␤-2 Adrenergic receptors (B2ARs) are endocytosed by clathrin-coated pits. This process serves specialized functions in signal transduction and receptor regulation, raising the question of whether B2ARs are associated with biochemically specialized membrane vesicles during their endocytic trafficking. Here we show that B2ARs are endocytosed by a distinct subpopulation of clathrin-coated pits, which represent a limited subset of coated pits present in the plasma membrane, even in cells overexpressing both B2ARs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 26 publications
10
104
1
Order By: Relevance
“…Finally, CB1-EGFP-positive vesicles do not significantly colocalize with organelles associated with synthesis (Golgi or ER) but rather resemble endocytic vesicles (endosomes) like those positive for TfR. The fact that only few endosomes contain both TfR and CB1R suggests that sorting events separate endocytosed CB1R and TfR, as described for the ␤ 2 -adrenergic receptor and the TfR (43). Interestingly, we also detect clear segregation between CB1R and TfR in a downstream portion of the endocytic pathway, where CB1Rs avoid Rab11-positive perinuclear recycling endosomes, whereas TfRs are enriched in this compartment.…”
Section: Cb1r Is Constitutively Endocytosed and Am281-induced Externamentioning
confidence: 91%
“…Finally, CB1-EGFP-positive vesicles do not significantly colocalize with organelles associated with synthesis (Golgi or ER) but rather resemble endocytic vesicles (endosomes) like those positive for TfR. The fact that only few endosomes contain both TfR and CB1R suggests that sorting events separate endocytosed CB1R and TfR, as described for the ␤ 2 -adrenergic receptor and the TfR (43). Interestingly, we also detect clear segregation between CB1R and TfR in a downstream portion of the endocytic pathway, where CB1Rs avoid Rab11-positive perinuclear recycling endosomes, whereas TfRs are enriched in this compartment.…”
Section: Cb1r Is Constitutively Endocytosed and Am281-induced Externamentioning
confidence: 91%
“…Our results also suggest that the activation of GPR109A promotes the translocation of arrestins to the plasma membrane, where the receptor preferentially binds arrestin3 rather than arrestin2. Therefore, together with the observation that treatment with hypertonic sucrose (0.45 M) inhibited GPR109A internalization, we postulate that phosphorylated GPR109A binds arrestin3 after receptor activation, is targeted to clathrin-coated pits, and is then rapidly recycled back to the cell surface from perinuclear early endosomes after internalization (43,44). Walters et al (45) reported that niacin-induced stimulation of GPR109A led to arrestin-dependent signaling to ERK1/2 activation, and this pathway mediated the adverse side effect of cutaneous flushing but not the beneficial antilipolytic effect of niacin.…”
Section: Discussionmentioning
confidence: 99%
“…The immobile receptors are probably in the process of internalization inside clathrin-coated pits (41). Receptors located inside clathrin-coated pits are thought to be tightly packed and immobile (36), and coated pits themselves are believed to be attached to the membrane skeleton, inasmuch as the formation of coated pits repeatedly occurs at defined sites of the plasma membrane (42).…”
Section: Discussionmentioning
confidence: 99%